If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 4 + -2x + -7 = -23 Reorder the terms: 4 + -7 + 7x + -2x = -23 Combine like terms: 4 + -7 = -3 -3 + 7x + -2x = -23 Combine like terms: 7x + -2x = 5x -3 + 5x = -23 Solving -3 + 5x = -23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5x = -23 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = -23 + 3 5x = -23 + 3 Combine like terms: -23 + 3 = -20 5x = -20 Divide each side by '5'. x = -4 Simplifying x = -4
| 27x^3+27x^2+9x+1= | | 16x^2+18=-609 | | 15000-500x+4x^2=0 | | 1=5-v | | (8+4i)-(9-3i)= | | x=10-6y | | (x,4),(6,-1)= | | 6x=4x-6 | | 15000-500x+4x^2=10400 | | 6g+4=58 | | -5x^2-38x-21=0 | | 2(q-4)=6 | | 3x=3*2+x*2 | | 4y+3=-3+2y+14 | | 2.25=qt | | 1-3x=2(-4x+7) | | 4a+2b=5 | | -10=-4+2k | | -5(x-4)-9=11 | | 14=8+2p | | 7(2x+5)=4x | | 10b^2-11b+3=0 | | 16=3s-4 | | 5+7i^2= | | (5x^2-7x-2)+(9x^2+8x-4)= | | 5(3y-1)-3(2x)=19 | | 6+3s=-9 | | 3m^2+6=-36 | | 3q+1=10 | | 2(n-6)=24 | | -6x+4=-4(2x+3) | | 2+3(x+1)=5x+5 |